Goat production in Barangay Pandaraonan Nueva Valencia, Guimaras and its marketability - Ombao, Ma. Corazon C.
This study, " Goat production in barangay Pandaraonan, Nueva Valencia-Guimaras and its marketability" was undertaken to answer the question on the conduciveness of Barangay Padaraonan or the whole of Guimaras in producing or raising goats since the island is rich in forage grasses. Moreover, the study was undertaken to answer the question on the marketability of goats by determining the supply and demand of goats in Guimaras and Iloilo City respectively. Lastly, the research would provide a basis for the Landbank of the Philippines to grant or provide additional financial assistance to the existing goat producers and cooperatives who may wish to enter endeavor such as goat production.